Protecting Student Records and Facilitating Education Research: A Workshop Summary - Hilton, Margaret (National Academies Press, 2009)
Designed to protect the privacy of individual student test scores, grades, and other education records, the Family Educational Rights and Privacy Act (FERPA) of 1974 places limits the access of educational researches, and slows research not only in education but also in related fields, such as child welfare and health. Recent trends have converged to greatly increase the supply of data on student performance in public schools. Education policies now emphasize education standards and testing to measure progress toward those standards, as well as rigorous education research. At the same time, private firms and public agencies, including schools, have replaced most paper records with electronic data systems. Although these databases represent a rich source of longitudinal data, researchers' access to the individually identifiable data they contain is limited by the privacy protections of FERPA. To explore possibilities for data access and confidentiality in compliance with FERPA and with the Common Rule for the Protection of Human Subjects, the National Academies and the American Educational Research Association convened the Workshop on Protecting Student Records and Facilitating Education Research in April 2008.